A Pilot Randomized Control Trial to Assess the Impact of Lavender on Anxiety and Comfort After Cesarean Birth and the Barriers Encountered. Issue 2 (March 2022) - Burgess, Adriane; Harris, Amy; Wheeling, Julia
Abstract: Purpose: This study aimed to assess the effect of lavender aromatherapy on anxiety and comfort after cesarean birth. Study Design: Randomized control trial. Methods: Forty-eight patients who had a cesarean birth were asked to complete the six-item State and Trait Anxiety (STAI-6) score to assess their level of anxiety pre- and postapplication of either lavender aromatherapy or placebo during their inpatient postpartum stay. Their comfort and pain levels pre- and postadministration were assessed, and differences between groups were analyzed. Results: There was no difference in postintervention STAI-6 scores between the aromatherapy and placebo groups ( p = .56). Women who received the lavender aromatab ® had significantly ( p = .037) higher self-reported levels of comfort ( M 2.6 SD .82) when compared with those who received placebo ( M 2.0 SD 1.0). Clinical Implications: Many women use aromatherapy at home to promote comfort and relaxation. Women feel lavender aromatherapy improves their comfort in the hospital setting after cesarean birth. Clinicians should consider ways to safely use aromatherapy as one option to promote postoperative cesarean birth care. Abstract : Aromatherapy can be an option for pain relief and comfort measures for women after cesarean birth. In this randomized controlled clinical trial, women were offered lavendar tablets or a placebo in the early hours after cesarean birth when they were admitted to the mother-baby unit. Women found the lavendar to be a comforting postcesarean intervention. These hospital-based nurse scientists share their experiences in conducting a randomized controlled clincal trial in a community hospital.